Two Delegations of British Architects in the Soviet Union: Professional Contacts between British and Soviet Architects at the Beginning of the Khrushchev Thaw - Malich, Ksenia A. (Actual Problems of Theory and History of Art, 2021)
The article is devoted to the history of professional contacts between British and Soviet architects at the beginning of the Khrushchev Thaw period. A great deal of work that has been carried out in recent decades in the field of studying the activities of the VOKS and Soviet cultural international politics, as well as a discussion about the features and the role of Soviet architectural practice in the 1930–1950s, prompt us to look at this subject with special attention. After all, the reasons, circumstances, and the very nature of professional communication between Russian architects and their foreign colleagues help us to take a fresh look at the peculiarities of the development of post-war architecture. Before World War II, some British architects, although they considered the possibility of travelling to the USSR in hope of getting an order, mostly came here out of curiosity. However, in the 1940s, the context of the perception of the Soviet art changed. The tasks of post-war reconstruction were common to both Great Britain and the USSR: the industrialization of the construction sector, mass housing, the redevelopment of cities, and the restoration of damaged historical monuments. Intensive communication between the VOKS architectural section and English architects already during the war years predetermined the mutual interest that flared up in the post-war period. The first trips, which took place in 1953 and 1955, as well as their results, have been reviewed in this study.The publication was prepared within the framework of the Academic Fund Program at HSE University in 2020–2021 (grant № 20-04-029).
Keywords: VOKS; cultural diplomacy; Soviet architecture; British architecture; Lubetkin; London architectural Association